Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada PT. Pegadaian - Erlina Ali Marpaung; Ella Fiana br Sitohang; Farah Dilla; Hasyim Hasyim (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research investigates the impact of service quality on customer satisfaction at PT. Pawnshop. Through analysis of survey data, it was found that service quality, including responsiveness, reliability, assurance, empathy, and physical evidence, positively influences customer satisfaction. These results provide insight for PT. Pawnshops to improve their services, strengthen ties with customers, and increase customer satisfaction. The type of research used in this research is qualitative research with descriptive methods. The descriptive method is considered suitable for explaining the influence of service quality on customer satisfaction at PT. Pawnshop. The data in this research report was obtained in accordance with books, journals, articles, theses, the internet and so on related to the research topic. The results of the research and discussion can be concluded from the five dimensions of service quality, the most important dimension for customers is guarantee, because customers prioritize security, comfort and trust in transactions with PT. Pawnshop. Conclusion This research has the implication that PT. Pegadaian must maintain and improve service quality to achieve higher customer satisfaction. PT. Pegadaian must also strengthen relationships with customers by providing services that are in line with customer expectations and needs